1991
DOI: 10.1111/j.1467-954x.1991.tb00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Football Hooligans: Theory and Evidence

Abstract: bstractThis paper describes empirical research amongst hooligans. Such research has not always been valued. The significant factor in hooligan behaviour may be asserted to be the generation of violence in the lower working class and its dissemination amongst football fans. It is commonly asserted that hooligans operate in well-organized groups. It is argued here that such assertions need to be based on better evidence. A detailed account is given of the behaviour of a notorious group of fans and its key indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 1 publication
0
33
0
3
Order By: Relevance
“…Previous detailed empirical research into football culture and football hooliganism demonstrates the strengths of the case study method (e.g. Marsh et al, 1978;Armstrong and Harris, 1991;Armstrong, 1998;Robson, 2000). A problem with these investigations is that their emphasis on empirical data in a specific geographical area may make the findings difficult to generalize to another time or place (Bailey, 1994: 58), although, as Flyvbjerg (2001) rightly argues, this is not necessarily the case.…”
Section: A Methodological Notementioning
confidence: 99%
See 2 more Smart Citations
“…Previous detailed empirical research into football culture and football hooliganism demonstrates the strengths of the case study method (e.g. Marsh et al, 1978;Armstrong and Harris, 1991;Armstrong, 1998;Robson, 2000). A problem with these investigations is that their emphasis on empirical data in a specific geographical area may make the findings difficult to generalize to another time or place (Bailey, 1994: 58), although, as Flyvbjerg (2001) rightly argues, this is not necessarily the case.…”
Section: A Methodological Notementioning
confidence: 99%
“…Nevertheless, the theoretical framework and methodology employed by Dunning and his colleagues have been criticized on various occasions (e.g. Armstrong, 1998;Armstrong and Harris, 1991;Giulianotti, 1999). It has been suggested that their theoretical approach operates on a high level of generality and has an aura of universalistic applicability and 'irrefutability' (Williams, 1991: 177).…”
Section: The Figurational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethnographic work of Armstrong and Harris (1991) has led to a useful debate among leading researchers in the eld about the key issues facing researchers when analysing the social context and everyday practices of 'football hooligans' (Dunning, Murphy and Waddinston 1991;Hobbs and Robins 1991). But these studies do not provide a rounded analysis of the development and role of racist cultures in football.…”
Section: Football Culture Racism and The 'Hooligan Debate'mentioning
confidence: 99%
“…Turner 1974;Bauman 1992) and exists as one of the anthropologist Maffesoli's (1991: 12) postmodern 'neo-tribes' which 'attract and collide with each other in an endless dance, forming themselves into a constellation whose vague boundaries are perfectly fluid' (cf. Armstrong and Harris 1991;Giulianotti 1993).…”
Section: Football Hooligan Gatherings Resource Network Of Time Idementioning
confidence: 99%